"Why Make a Special Platoon for Women?": An Assessment of the Jegertroppen at the Norwegian Special Operations Commando (NORSOC). Issue 1 (2nd January 2019) - Steder, Frank Brundtland; Rones, Nina
Abstract : In 2014, the Norwegian Special Operations Commando (NORSOC) established a pilot project named "Jegertroppen" (the Hunter Troop) to recruit more women for operative military service. This unusual approach, integration of women by separating men and women during education, brought national and international attention, including admiration and wonder. This article explores why NORSOC segregated male and female operators, and assess the effectiveness of the segregated approach for recruiting, selecting, and retaining female operators.